USING AUTHENTIC MATERIALS IN IMPROVING READING COMPREHENSION - Nadya; R. Mertosono, Sudarkam; Dewi, Anjar Kusuma; Arid , Muhammad (Tadulako University, 2024)
This study aims to know whether or not using authentic materials can improve reading comprehension of the grade eight students of SMP Negeri 16 Palu. This research used a quasi-experimental research design. The research population was the grade eight students of SMP Negeri 16 Palu which consisted of 112 students. The sample was selected by using a purposive sampling technique. The number of the sample was 22 students of class VIII A as the experimental group and 22 students of class VIII E as the control group. The data were collected through pre-test and post-test about reading. The students were assigned some tasks consisting of 10 multiple-choices and 5 essay questions. The result of this research showed the mean deviation score of the experimental group was 89.45 and 79.27 for the control group. Therefore, the t-counted value (6.43) is higher than the t-table value (2,018). It is proved that the hypothesis is accepted in which there is development of the students after getting the treatment. It means that the use of Authentic Materials can improve students Reading comprehension. The implication of this finding is that the teachers need to use authentic material as the media in teaching reading.